2012
DOI: 10.1038/mt.2012.164
|View full text |Cite
|
Sign up to set email alerts
|

Ribosomal DNA Integrating rAAV-rDNA Vectors Allow for Stable Transgene Expression

Abstract: Although recombinant adeno-associated virus (rAAV) vectors are proving to be efficacious in clinical trials, the episomal character of the delivered transgene restricts their effectiveness to use in quiescent tissues, and may not provide lifelong expression. In contrast, integrating vectors enhance the risk of insertional mutagenesis. In an attempt to overcome both of these limitations, we created new rAAV-rDNA vectors, with an expression cassette flanked by ribosomal DNA (rDNA) sequences capable of homologous… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
29
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(29 citation statements)
references
References 49 publications
0
29
0
Order By: Relevance
“…The first attempts to combine the targeted integration ability of zinc fingers with SB transposons consisted of adding a zinc-finger DNA-binding domain to SB transposase [198, 199], which resulted in diminished SB activity and marginal targeting. More recent approaches have employed either a targeted zinc-finger nuclease-mediated double-strand DNA break [200], the adeno-associated virus Rep protein [201] or targeting ribosomal RNA genes [202, 203]. Both strategies report better outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…The first attempts to combine the targeted integration ability of zinc fingers with SB transposons consisted of adding a zinc-finger DNA-binding domain to SB transposase [198, 199], which resulted in diminished SB activity and marginal targeting. More recent approaches have employed either a targeted zinc-finger nuclease-mediated double-strand DNA break [200], the adeno-associated virus Rep protein [201] or targeting ribosomal RNA genes [202, 203]. Both strategies report better outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…AAV genomes containing transgenes flanked by homology to target loci are capable of stimulating HDR in the absence of a nuclease, albeit at lower rates 48,86,120-122 . Using this strategy one study targeted a factor IX cDNA to the highly expressed albumin locus, allowing for correction of the bleeding diathesis phenotype in factor IX deficient mice 62 .…”
Section: Challenges To Clinical Translationmentioning
confidence: 99%
“…By using the nonviral delivery method, the absolute targeting frequency is more than 20-fold higher than that in HT1080 cells at HPRT , a most commonly targeted locus [34]. In previous reports, by including 28S rDNA homology arms into the vector design, the integration frequency of a recombinant adeno-associated viral vector in rat hepatocytes was enhanced by 30-fold [10]. The underlying mechanism appears to be the relatively high intrinsic activity of HR at the rDNA locus.…”
Section: Discussionmentioning
confidence: 99%
“…Targeting an exogenous gene into one or a few of the rDNA repeats may not cause loss of function effects of the rRNA genes owing to high copy number of this gene. These properties indicate that the rDNA locus may hold a high intrinsic homologous recombination (HR) activity and this locus is considered to be an ideal safe locus for transgene integration [10, 11]. Several studies have reported that efficient targeted gene addition at the rDNA 28s locus could be achieved based on viral transfer methods.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation